An Injectable Hydrogel Platform for Sustained Delivery of Anti-inflammatory Nanocarriers and Induction of Regulatory T Cells in Atherosclerosis - Yi, Sijia; Karabin, Nicholas B.; Zhu, Jennifer; Bobbala, Sharan; Lyu, Huijue; Li, Sophia; Liu, Yugang; Frey, Molly; Vincent, Michael; Scott, Evan A. (Frontiers in Bioengineering and Biotechnology, 2020)
Chronic unresolved vascular inflammation is a critical factor in the development of atherosclerosis. Cardiovascular immunotherapy has therefore become a recent focus for treatment, with the objective to develop approaches that can suppress excessive inflammatory responses by modulating specific immune cell populations. A benefit of such immunomodulatory strategies is that low dosage stimulation of key immune cell populations, like antigen presenting cells, can subsequently propagate strong proliferation and therapeutic responses from effector cells. We have previously demonstrated that intravenous injections of anti-inflammatory nanocarriers provided atheroprotection that was mediated by regulatory T cells (Tregs) upregulated in lymphoid organs and atherosclerotic lesions. Here, we demonstrate an injectable filamentous hydrogel depot (FM-depot) engineered for low dosage, sustained delivery of anti-inflammatory nanocarriers. The bioactive form of vitamin D (aVD; 1, 25-Dihydroxyvitamin D3), which inhibits pro-inflammatory transcription factor NF-κB via the intracellular nuclear hormone receptor vitamin D receptor (VDR), was stably loaded into poly(ethylene glycol)‐block‐poly(propylene sulfide) (PEG-b-PPS) filomicelles. These aVD-loaded filaments underwent morphological transitions to release monodisperse drug-loaded micelles upon oxidation. This cylinder-to-micelle transition was characterized in vitro by cryogenic transmission electron microscopy (CryoTEM) and small angle X-ray scattering (SAXS). Following crosslinking with multi-arm PEG for in situ gelation, aVD-loaded FM-depots maintained high levels of Foxp3+ Tregs in both lymphoid organs and atherosclerotic lesions for weeks following a single subcutaneous injection into ApoE-/- mice. FM-depots therefore present a customizable delivery platform to both develop and test nanomedicine-based approaches for anti-inflammatory cardiovascular immunotherapy.